Pengaruh Citra Merk, Desain Produk Dan Persepsi Harga Terhadap Keputusan Pembelian Smartphone Samsung Di Kota Bogor - Herlan Herlambang; Mumuh Mulyana; Febry Lodwyk Rihe Riwoe (Jurnal Informatika Kesatuan, 2022)
The purpose of this study was to determine the effect of Brand Image, Product Design and Price Perception on Samsung smartphone Purchase Decisions in Bogor city. The number of samples used in this study amounted to 200 respondents taken from users or those who have used smartphone Samsung. The tool used to collect data is a questionnaire and the data in this study were processed using SPSS version 21. The results of the analysis show that (1) Brand Image has a positive and significant effect on purchasing decisions with a t-count of 6,945, which is greater than t-table 1.65 and a significant value of 0.000 <0.05. (2) Product Design has a positive and significant effect on purchasing decisions with a t-count of 3,708, which is greater than t-table 1.65 and a significance value of 0.000 <0.05. (3) Product quality has a positive and significant effect on purchasing decisions with a t-count of 2,017, which is greater than t-table 1.65 and a significance value of 0.045 <0.05. (4) Brand Image, Product Design and Price Perception together have a positive and significant relationship to Purchase Decisions with an f-count of 29,567, which is greater than f-table 2.65 and a significance value of 0.000 <0.05. Keywords: Brand Image, Product Design and Price Perception on Purchase Decision